Implementation Of SIPD in Budget Planning at BPKAD Palu City - Fitria; Femilia Zahra; Jurana; Masruddin (LP2M IAIN Palopo, 2026)
To improve regional financial management, the government has implemented a Regional Information System (SIPD). This study aims to analyze the implementation of SIPD in the budget planning process at the Palu City Regional Financial and Asset Management Agency (BPKAD), while identifying obstacles encountered and corrective measures to improve the quality of its implementation. The approach used in this study is a descriptive qualitative method by collecting data through observation, documentation studies and interviews, and making the Palu City BPKAD Office the research object. Data analysis was carried out referring to the analysis model of Miles and Huberman (1984). The results of this study indicate that the implementation of SIPD at the Palu City BPKAD has been going quite well, efficiently and effectively, although it still requires further development. These findings are evident in the increased efficiency and accountability in the budget planning process. The main obstacles identified include system delays when accessed simultaneously by multiple users, internet connection disruptions, and potential server overload. Addressing efforts are carried out through regular data backups, coordination with the development team for bug reporting, improving network stability, updating devices and infrastructure, and holding regular discussion forums with the Palu City Regional Apparatus Organizations (OPD). Keywords : Regional Financial and Asset Management Agency (BPKAD); Palu City; Budget Planning; Regional Information System (SIPD)